EVALUASI PROGRAM KAMPUS MENGAJAR PADA SMPN 3 SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - Afriaji, Muhammad; Rahmayanti, Anita (SINERGI : Jurnal Riset Ilmiah, 2025)
Education plays a crucial role in developing high-quality human resources. In Indonesia, the Kampus Mengajar Program was launched as part of the Merdeka Belajar policy to enhance education quality, particularly in under-resourced schools. This study aims to evaluate the implementation of the Kampus Mengajar Program at SMPN 3 Sungai Pandan, Hulu Sungai Utara Regency, using the CIPP (Context, Input, Process, Product) evaluation model. The research focuses on the program's impact on learning quality, the role of students in supporting teachers, and the responses from students, teachers, and the community. The findings reveal that the program has positively impacted students' learning motivation, strengthened literacy and numeracy skills, and introduced innovative teaching methods. However, challenges such as limited implementation time, insufficient training, and logistical constraints need to be addressed to improve program effectiveness. Based on these findings, it is recommended that universities enhance pre-program training, increase mentoring support, and improve coordination between students and schools. Continuous support from local governments is also necessary to sustain the program's impact. With improvements in these areas, the Kampus Mengajar Program is expected to make a more significant contribution to achieving quality education in remote areas.